Laser diagnosis of gas turbine fuel sprays; scaling effects on NOx emissions and stability - Hussain, Mazhur (Cranfield University, 2009)
This thesis first provided strategic recommendations for the research sponsor, Rolls- Royce plc (RR) and then applied optical diagnostics to measure aero gas turbine fuel spray properties in order to predict Oxides of Nitrogen (NOx) emissions and combustion instability. Analysis of the large civil aero engine sector suggested possible courses of action for RR to protect itself from short-term market volatilities and also prepare for three long term changes in strategic operating context: air traffic growth; tighter United Nations enforced aero engine combustion emissions legislation and entry of civil aviation into the European Union Emissions Trading Scheme. A collaborative game theoretic approach was explored during the pre-competitive, pre-technology, capability acquisition aero engine design phase on unproven future technologies to reduce R&D expenditures, development times and the costs of failure. Lean Prevapourised Premixed combustion demands excellent spray atomisation quality to sustain combustion efficiency, stability and to minimise pollutants. Post development of an improved procedure to calibrate laser signals, methodology to predict NOx and technique to optimise rig operating conditions that minimised fractional discrepancies in two-phase flow behaviour with corresponding engine conditions, this thesis applied quantitative Planar Laser Induced Fluorescence (PLIF) and Laser Sheet Dropsizing (LSD) to measure the fuel placement and dropsize distribution in the near nozzle regions of RR liquid-fuelled hybrid, airblast and pressure-swirl sprays. Measurements were made under non-combusting, low pressure conditions and results were processed to identify fuel injector designs that exhibited low emissions and high stability for the Affordable Near Term Low Emissions (ANTLE) and Instability Control of Low Emission Aero-Engine Combustors (ICLEAC) engine demonstrator programmes. Results also provided validation data and boundary conditions for spray computational codes. Research findings will improve RR core competencies in fuel injection research to accelerate the development and deployment of low emissions aero engine technology.